The Importance Of Character Education In Building A Resilient Nation - Elsa Yulia Fitriyani; Nur Uyuni; Lucyus Gultom; Widia Anggelina; Muhammad Gita Permana; Muhammad Yogi Triyadi; Masduki Asbari; Agus Purwanto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
Character education is a system of inculcating character values ​​in the form of knowledge, will, and behaviors that are following the values ​​of belief in God, oneself, fellow environment, and nationality. For this reason, the priority of national development is to strive for the formation of pious Indonesian people who obey the rule of law, develop social morals, apply the noble values ​​of the nation's culture, and have a nationality as the Indonesian nation to strengthen the spiritual, moral and ethical foundation of nation-building. From the exposure to various expert opinions about character, it can be concluded that character is a distinctive trait possessed by a person that contains values, abilities, and moral capacities, in thinking and acting which are formed from habits carried out when interacting with others people in the daily environment. Family and Community Day character education improve and strengthen the role of families, education units, communities, and the government to participate and be responsible for developing the potential of citizens and building the nation towards an advanced, independent, and prosperous nation.